Uang dalam Perspektif Ekonomi Islam - Abd Ghafur (Fakultas Ekonomi dan Bisnis Islam, 2017)
When the number of people growing and the advance of civilization, activity, as well as the inbraclions among humans is incresing. The number and types ot human needs is also increasingly drverse. One another began to require. Then needed a medium of exchange which was then known as “Money”. After the presence of money, the mashet began to form as a meeting place for buyers and sellus to transact with each other goods and services. Initrally the fuction of money is just a medium of exchange is order to facititate the exchange of. Put, along ajth the times of money has switehed from medium of exchenge to a broader function plper. Money in Islamic economics is a flow concept, where the treasures should hot be stacked but rather owned property shall be circulated. In Islam, anything that serves as money then the fuuction ouly as a medium of exchange, not a commodity that is traded whit exchange ether on the spot or not.